New reading 360: picnic for tortoise - Piggins, Bill; Root, Betty (Ginn ,Pearson Harlow, 1993)
The New Reading 360 series is designed to provide a solid literary foundation for infants and build on previous literacy knowledge for juniors. Readers help to develop literacy skills and build up confidence.